(untitled) (Archaeologia Adriatica, 2022)
The newly proposed typological scheme of Iapodian and Liburnian anthropomorphic pendants allows for a fresh look at – and new findings about – this interesting ornament type. The original, earliest and most broadly distributed pendant type appears to be that of Prozor, with analogies also on the opposite side of the Adriatic, in present-day Italy. It spread across the Iapodian and Liburnian territories, from where individual specimens reached Bela Krajina and eastern Dolenjske. They can be dated to the period from the eighth until the sixth century. In Lika, earlier forms were worn sewn on certain parts of the attire, for example caps and/or belts, while later ones were worn as pectorals. Liburnians probably also wore them as earrings. Of course, it is not excluded that individual specimens were used as separate objects, such as amulets, especially outside the Iapodian territory. It is a geographically very limited type of ornament; however, only this one fits into the scheme of potnia theron form pendants, represented on the 7th century Apennine Peninsula in several forms.